Interdecadal variability of the south american precipitation in the monsoon season - Grimm, A.M. and Saboia, J.P.J. (My University, 2014)
Interdecadal variability modes of monsoon precipitation over South America (SA) are provided by a continental-scale rotated empirical orthogonal function analysis, and their connections to well-known climatic indices and SST anomalies are examined. The analysis, carried out for austral spring and summer, uses a comprehensive set of station data assembled and verified for the period 1950&ndash2000. The presented modes are robust, consistent with previous regional-scale studies and with modes obtained from longer time series over smaller domains. Opposite phases of the main modes show differences around 50% in monthly precipitation. There are significant relationships between the interdecadal variability in spring and summer, indicating local and remote influences. The first modes for both seasons are dipole-like, displaying opposite anomalies in central-east and southeast SA. They tend to reverse polarity from spring to summer. Yet the summer second mode and its related spring fourth mode, which affect the core monsoon region in central Brazil and central-northwestern Argentina, show similar factor loadings, indicating persistence of anomalies from one season to the other, contrary to the first modes. The other presented modes describe the variability in different regions with great monsoon precipitation. Significant connections with different combinations of climatic indices and SST anomalies provide physical basis for the presented modes: three show the strongest connections with SST-based indices, and two have the strongest connections with atmospheric indices. However, the main modes show connections with more than one climatic index and more than one oceanic region, stressing the importance of combined influence.
Keywords: Climatology, Decadal variability, Interdecadal variability